Optimization of the production conditions of glutinous rice bran protein hydrolysate with antioxidative properties - Warintip Sarringkarin (2018)
Glutinous rice bran (GRB) is a byproduct of milling rice. Because of its high protein content, GRB can be used to produce protein hydrolysate with antioxidative properties. The antioxidant activity of protein hydrolysate depends on hydrolysis conditions. In this study, protein from GRB cv. RD6 was prepared and then subjected to proteolytic hydrolysis by alcalase. The hydrolysis conditions were optimized using response surface methodology (RSM). We investigated two independent variables: the enzyme to substrate (E/S) ratio (0.59-3.41%, w/w) and the time taken for hydrolysis to occur (45-555 minutes). The E/S ratio and hydrolysis time significantly affected the yield, DPPH radical scavenging activity, metal chelating activity, degree of hydrolysis (DH), and average molecular weight (MW) of the protein hydrolysates. The optimum conditions for hydrolysis were an E/S ratio of 2.84% and 480 minutes for hydrolysis, which obtained a yield of 40.73 ± 0.44%, an IC 50 value of 0.87 ± 0.02 mg/ml in the DPPH assay, a metal chelating activity of 72.80 ± 1.79%, a DH of 22.18 ± 0.42% and a MW of 3.07 ± 0.14 kDa. GRB protein hydrolysate, produced using alcalase, could have potential applications as an ingredient in functional food products due to its high antioxidative properties.